Cyndi Lauper : a memoir - Lauper, Cyndi, 1953- (Atria Books, 2012)
"Legendary and iconic singer-songwriter Cyndi Lauper offers a poignant account of the journey that led her to become an international superstar--from her years growing up in Queens, New York, to the making of enduring hits like 'Time after time,' 'Girls just want to have fun,' and 'True colors,' to becoming an actress, a mother, an outspoken activist, and maintaining a music career that has lasted more than thirty years"--From publisher description.